Preparation, Characterization and in vitro Antimicrobial Activities of Chinese Herbs Incorporated Edible Starch Films - Li1, Dehai; Yang1, Lei; Wang1, Ping; Song2, Wei; Hou1, Enling; Zuo1, Chunyang (Asian Journal of Chemistry, 2013)
Films made of corn starch and Chinese medicinal herbs with antibacterial activity on Escherichia coli were developed. Influences of concentration of Chinese medicinal herbs on performances of the films were investigated based on indicators of antibacterial effects, absorbance, extensibility and moisture resistance. Moreover, the optimal concentration was determined. Scutellaria baicalensis and Schisandra chinensis stood out in the antibacterial test, with the MIC values of 0.7813 and 1.5625 mg/mL respectively. The addition of herbs increased antibacterial effectiveness and absorbance, meanwhile decreased extensibility and moisture resistance. To ensure the antibacterial effects and mechanical properties, concentration of Scutellaria baicalensis can be added in the film with MIC~4MIC (including MIC and 4MIC) and Schisandra chinensis with MIC~2MIC (not including MIC and 2MIC).